4(y-7)=5-(6y-2)

Simple and best practice solution for 4(y-7)=5-(6y-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(y-7)=5-(6y-2) equation:


Simplifying
4(y + -7) = 5 + -1(6y + -2)

Reorder the terms:
4(-7 + y) = 5 + -1(6y + -2)
(-7 * 4 + y * 4) = 5 + -1(6y + -2)
(-28 + 4y) = 5 + -1(6y + -2)

Reorder the terms:
-28 + 4y = 5 + -1(-2 + 6y)
-28 + 4y = 5 + (-2 * -1 + 6y * -1)
-28 + 4y = 5 + (2 + -6y)

Combine like terms: 5 + 2 = 7
-28 + 4y = 7 + -6y

Solving
-28 + 4y = 7 + -6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6y' to each side of the equation.
-28 + 4y + 6y = 7 + -6y + 6y

Combine like terms: 4y + 6y = 10y
-28 + 10y = 7 + -6y + 6y

Combine like terms: -6y + 6y = 0
-28 + 10y = 7 + 0
-28 + 10y = 7

Add '28' to each side of the equation.
-28 + 28 + 10y = 7 + 28

Combine like terms: -28 + 28 = 0
0 + 10y = 7 + 28
10y = 7 + 28

Combine like terms: 7 + 28 = 35
10y = 35

Divide each side by '10'.
y = 3.5

Simplifying
y = 3.5

See similar equations:

| C=39.45+0.25x | | 8z=3 | | 7(4x+2)=42 | | X^2-4x=5x | | 2.5k+5-1.5.5k=14 | | x^2+2x-363=0 | | 4x-8=7+3 | | v=Ixt | | z^3-z^2-6=0 | | 3y=0.006 | | 6=10c | | 1-5x=x-13 | | Log(x+4)=8 | | (2x)=1 | | Y-(-12)=7 | | 12x-6=-11x | | x^2-18x=1.25 | | 4(5x-8)-3(2x-7)= | | 9(9x)=96x | | 8x=(3x^2)-2 | | 7x-3=4x-24 | | (6f-k)= | | 36m^6+12m^4=m^2+0 | | 8r^2+10r-12=0 | | 10x+3=100 | | 5[3(x+4)-2(1-x)]-x-35=14x+65 | | 1.3-5r=7.8 | | 250x^3+128= | | 5y+6y-81=7y+102+66y | | 4a=3a+20 | | fx=(400+20x)(90-1x) | | (3q-8)(-9q+2)(q-2)=0 |

Equations solver categories